2004
DOI: 10.1111/j.1742-7843.2004.pto950107.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Patient Questionnaires and Plasma Assays in Intentional Drug Overdoses

Abstract: Our aim was to explore the agreement between clinically collected information on purported drug intake and plasma data in intentional drug overdose. We included all subjects with intentional drug overdose above 15 years of age consecutively admitted to the Emergency Department of the University Hospital during 4 months. Information about drugs used and sources of this information was collected and compared to presence of drug in plasma, concerning four drugs with high toxic potential (tricyclic antidepressants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
(44 reference statements)
1
9
0
2
Order By: Relevance
“…Whenever possible, history gathering should include questioning of persons who accompany the patient, evaluation of containers, review of pharmacy records, and examination of the patient's prior medical record. 220 Many patients who ingest medications in a suicide attempt take more than 1 substance, and the number of substances ingested is greater in fatal than in nonfatal suicide attempts. 221 Comprehensive toxicology laboratory testing is virtually never available in a time frame that supports early resuscitation decisions.…”
Section: Initial Approach To the Critically Poisoned Patientmentioning
confidence: 99%
“…Whenever possible, history gathering should include questioning of persons who accompany the patient, evaluation of containers, review of pharmacy records, and examination of the patient's prior medical record. 220 Many patients who ingest medications in a suicide attempt take more than 1 substance, and the number of substances ingested is greater in fatal than in nonfatal suicide attempts. 221 Comprehensive toxicology laboratory testing is virtually never available in a time frame that supports early resuscitation decisions.…”
Section: Initial Approach To the Critically Poisoned Patientmentioning
confidence: 99%
“…In a Finish study, 16% of acutely hospitalised patients had a positive benzodiazepine screening whereof 33% admitted use (NPV=89%) (9). Patients presenting in emergency departments are considerably younger of age but have also been found to report substance use with intermediate sensitivity (4,15,17).…”
Section: Discussionmentioning
confidence: 97%
“…This especially happened for legal drugs (benzodiazepines, methadone and opiates) and may be explained by either exaggerated reporting (16,17) or more likely by pharmacokinetic circumstances due to fast elimination half lives of used drugs, diluted urine, etc. (10,15).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Tricyclic antidepressants and paracetamol were found to be less commonly used in previous studies, while a higher frequency of simultaneous usage of alcohol was found. 5 The higher frequency of tricyclic antidepressants could be attributed to the fact that these drugs are old antidepressants that are not commonly used overseas, but commonly used in South Africa.…”
Section: Common Agents Usedmentioning
confidence: 99%